Renal calculus complicated with squamous cell carcinoma of renal pelvis: Report of two cases - Xiao, Jiantao; Lei, Jun; He, Leye; Yin, Guangming (Canadian Urological Association Journal, 2015)
Longstanding renal calculus is a risk factor of squamous cell carcinoma (SCC) of the renal pelvis. It is highly aggressive and usually diagnosed at advanced stages with a poor prognosis. We present two cases of kidney stone complications with renal pelvic SCC. These two patients had a radical nephrectomy and the dissected tissues were renal pelvic SCC. Our cases further emphasize that renal pelvic SCC should be considered in patients with longstanding renal calculus. These cases contribute greatly to an early diagnosis and early treatment, both of which will significantly minimize the damage of, and markedly improve the prognosis of, renal pelvic SCC.